Time Trends in Adolescent School Absences and Associated Bullying Involvement Between 2000 and 2019: A Nationwide Study - Alanko Katarina; Melander Katja; Ranta Klaus; Engblom Janne; Kosola Silja (Springer, 2025)
Education is a central determinant of adolescent health. School absences and bullying involvement jeopardize wellbeing, mental health, and educational attainment. We analyzed time trends in school absenteeism over two decades and examined the association of absenteeism with bullying involvement.We analyzed data from the nationwide School Health Promotion study, with self-reported data from Finnish middle school students in grades 8 and 9 (ages 14-17, N = 1 000 970). Questionnaires assessed frequency of illness absences (IA), truancy, frequency of bullying victimization, bullying perpetration, and involvement in both bullying perpetration and victimization. Frequent school absences were defined as occurring on more than 3 days during the prior month (2000-2015), or at least weekly (2017-2019).Frequent IA increased from 12% to 2000 to 22% in 2015. In 2017-2019, frequent IA was reported by 3.5%. Frequent truancy declined from 9% to 2000 to 4% in 2015, and remained at 4% during 2017-2019. Bully victimization was reported at least weekly by 6.9%, perpetration by 5.4% and victimization-perpetration by 1.9% of participants in total. In a logistic regression model, every type of bullying involvement increased odds for both IA and truancy.Since bullying involvement was associated with both IA and truancy, particular concern should be raised for adolescents involved in bullying, and for their social and educational functioning. The concurrent increase in IA and decrease in truancy may reflect destigmatization of mental health problems or other changes in reporting absenteeism.